The Wooden horse - Mackinnon, Mairi; Massari, Alida (Usborne Publishing Ltd UK, 2016)
Odysseus and the Greek army have fought the Trojans for ten long years. Will the war ever end? Finally, Odysseus thinks of a clever trick. Includes a word list, 5 pages of activities and free online audio (British English and American English). 800 headwords, 1,304 words